Assembled AU@PDA nanocrystals on reduced graphene oxide modified glassy carbon electrode for detection of multiplex DNA - Ng, Serene Shi Ya (2015)
We report here a successful multiplex DNA targets biosensor using reduced graphene oxide modified glassy carbon electrode (rGO-GCE). On the surface, a monolay of 50 nm Au@PDA nanocrystals were decorated on it. The modified Hummer’s method was used to chemically synthesize Graphene oxide (GO) and then electrochemically reduce to reduced graphene oxide (rGO). The rGO-GCE was obtained by reducing electrochemically in 0.1 M phosphate buffer solution at pH 7.0 via voltammetry cycling (2 cycles). Inspired by the composition of adhesive proteins in mussels, polydopamine film was formed by self-polymerizing dopamine and then adhered to the gold nanoparticles (Au NPs). Quantum dots (QDs) of metal sulfide nanocrystals (ZnS, CdS, PbS, CuS) were used as detection variable by dissolving the QDs which generates electrochemical signals that indicates the concentration of the DNA targets. The tests were carried out at the best condition of supporting electrolyte of sodium acetate (NaAc) at the concentration of 0.10 M and at the pH of 6.0. Multiplex DNA targets detection was successfully carried out with a linear range for DNA targets T1 (p16), T2 (p21), T3 (p53), and T4 (p73) ranging from 5 nM to 1 µM, 1 nM to 1 µM, 300 pM to 100 nM and 10 nM to 10 µM, with a detection limit of 2 nM, 300 pM, 100 pM and 3 nM, correspondingly. The study showed that even in the multiplex DNA detection, the electrode still displayed excellent selectivity and reproducibility.